Effect of Amplitude and Frequency on the Speed of Sound Waves in Air and Water Using PhET Simulation - Mulyaningsih, Rejeki Sri (Jurnal Pendidikan dan Ilmu Fisika, 2024)
Sound waves can occur not only in solid medium but also in air and water mediums. The effect of amplitude and frequency on the speed of sound waves differs between air and water mediums. The speed of sound waves cannot be seen with the naked eye. A virtual lab is needed to determine the speed of sound wave propagation. The purpose of this study is to determine the effect of amplitude and frequency on the speed of sound waves in air and water medium. The research method used is a quantitative method by conducting experiments online using the PhET application. PhET is used because it can carry out interactive simulations to facilitate research that cannot be done in real terms, but must make use of an effective virtual lab. The results obtained, namely in the medium of air and water, it is proven that the amplitude and frequency are directly proportional to the speed of sound wave propagation. In conclusion, sound waves travel faster in the water medium than in the air medium. Sound waves travel faster in the water medium because in liquid the particles are closer together than in the air medium, so sound waves will travel faster.